2007
DOI: 10.25011/cim.v30i2.984
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association polymorphisms of the IL1RN, IL1A, and IL1B genes with knee osteoarthritis in Turkish patients

Abstract: Clin Invest Med 2007; 30 (2): E86-E92. AbstractPurpose: To examine whether polymorphisms of the interleukin 1 receptor antagonist (IL1RN), interleukin 1 alpha (IL1A) and interleukin 1 beta (IL1B) genes are markers of genetic susceptibility to knee osteoarthritis in Turkish patients. Methods: One hundred and seven patients with knee osteoarthritis and 67 controls were studied. Three polymorphisms of IL1A, IL1B, and IL1RN genes were typed from genomic DNA. Allelic frequencies were compared between patients and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Several studies have also revealed contradictory findings of genetic contribution to OA. For example, a polymorphism in IL1RN was reported to be associated with disease severity in knee OA in a Caucasian population (Attur et al, 2010), while a study in a Turkish population found no association (Sezgin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also revealed contradictory findings of genetic contribution to OA. For example, a polymorphism in IL1RN was reported to be associated with disease severity in knee OA in a Caucasian population (Attur et al, 2010), while a study in a Turkish population found no association (Sezgin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes of rs1143634, rs16944 and rs419598 were determined by mass spectrometry (homogeneous Mass ARRAY 13,14 Ni et al 10 Ruzickova et al 11 Limer et al 7 Loughlin et al system; Sequenom Inc., San Diego, CA), using standard conditions. Genotypes were analysed by using Genotyper 3.0 software (Sequenom Inc.).…”
Section: Garp Studymentioning
confidence: 99%
“…Multiple genetic association studies have been undertaken to investigate whether these potential functional aspects of IL‐1 gene cluster polymorphisms may in part explain genetic susceptibility to OA. Previously, we and others have reported associations of the IL‐1 gene cluster with knee, hip, and hand OA (21–26), although others failed to confirm these associations (27, 28). Taken together, the findings to date indicate that the effects of IL‐1 gene cluster SNPs on innate ex vivo cytokine production and OA may be complex and may involve interactions among different polymorphic sites, and that they should therefore be investigated by studying independent haplotypes.…”
mentioning
confidence: 75%